2013
DOI: 10.1021/jm301848w
|View full text |Cite
|
Sign up to set email alerts
|

On Dihydroorotate Dehydrogenases and Their Inhibitors and Uses

Abstract: Proper nucleosides availability is crucial for the proliferation of living entities (eukaryotic cells, parasites, bacteria, and virus). Accordingly, the uses of inhibitors of the de novo nucleosides biosynthetic pathways have been investigated in the past. In the following we have focused on dihydroorotate dehydrogenase (DHODH), the fourth enzyme in the de novo pyrimidine nucleosides biosynthetic pathway. We first described the different types of enzyme in terms of sequence, structure, and biochemistry, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
188
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(190 citation statements)
references
References 251 publications
2
188
0
Order By: Relevance
“…Brequinar is an inhibitor of dihydroorotate dehydrogenase, the fourth enzyme of pyrimidine biosynthesis pathway, with a potent antiviral activity in vitro 30,31 . When looking at IC50 values, less than one order of magnitude separated this reference molecule from most active hits identified by screening.…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brequinar is an inhibitor of dihydroorotate dehydrogenase, the fourth enzyme of pyrimidine biosynthesis pathway, with a potent antiviral activity in vitro 30,31 . When looking at IC50 values, less than one order of magnitude separated this reference molecule from most active hits identified by screening.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Indeed, recent publications suggest that compounds targeting early steps of pyrimidine . In particular, research groups looking for antiviral molecules have found inhibitors of dihydroorotate dehydrogenase, the fourth enzyme of this metabolic pathway 31 . Uridine in culture medium efficiently trans-complements for the inhibition of this enzyme, and thus restores viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…DHODH has been suggested as a target for therapy in multiple diverse disease areas, including oncology, rheumatoid arthritis, multiple sclerosis, and infectious diseases caused by such agents as Plasmodium, bacteria, and viruses (21,29). There are currently two marketed agents that have activity against human DHODH: leflunomide for rheumatoid arthritis and teriflunomide for multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme activity of DHODH has been a highly investigated target for the development of inhibitors used to treat autoimmune diseases and for their use in treatments for cancer and virus and parasitic infections (34). In particular, significant progress has been made in identifying clinically relevant inhibitors of the Plasmodium DHODH that show promise for further clinical development in malaria treatment (10,11).…”
Section: Discussionmentioning
confidence: 99%